2009
DOI: 10.1007/s10577-009-9033-2
|View full text |Cite
|
Sign up to set email alerts
|

Physical mapping of rDNA and heterochromatin in chromosomes of 16 Coffea species: A revised view of species differentiation

Abstract: The chromosome organization among 15 wild diploid Coffea species and cultivated tetraploid C. arabica was determined by fluorochrome banding (CMA, DAPI) and double fluorescence in-situ hybridization (FISH) of 5S and 18S rDNA achieved on the same chromosome plates. Two to five chromosome pairs (plus one putative chromosome B) are marked. Overall, there are two SAT-chromosome pairs for East African species and one for the Malagasy and the West and Central African species. 18S rDNA loci are telomeric and strongly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 66 publications
5
50
0
Order By: Relevance
“…2), only one pair was marked after silver impregnation, which presumably would be number three, as observed by Pierozzi et al (1999) in C. canephora and in C. dewevrei. The presence of only one chromosome pair carrying nucleolar organizer region site in C. canephora, C. kapakata and P. travancorensis, has also been reported by Lombelo and Pinto-Maglio (2004 a, b) as well as in C. dewevrei by Hamon et al (2009), with the in situ hybridization with 45S rDNA probe. Conversely, C. racemosa and C. salvatrix showed silver impregnation (NOR band) in both chromosome pairs.…”
Section: Methodssupporting
confidence: 69%
See 2 more Smart Citations
“…2), only one pair was marked after silver impregnation, which presumably would be number three, as observed by Pierozzi et al (1999) in C. canephora and in C. dewevrei. The presence of only one chromosome pair carrying nucleolar organizer region site in C. canephora, C. kapakata and P. travancorensis, has also been reported by Lombelo and Pinto-Maglio (2004 a, b) as well as in C. dewevrei by Hamon et al (2009), with the in situ hybridization with 45S rDNA probe. Conversely, C. racemosa and C. salvatrix showed silver impregnation (NOR band) in both chromosome pairs.…”
Section: Methodssupporting
confidence: 69%
“…salvatrix displayed the highest mean values for THCL, χchrom, S (µm) and S%, however, the lowest valtempt to visualize and count the mitotic chromosomes of the ovules. Thenceforth, the studies developed in the genus of species ranged from the identification of the most probable genomes involved in the Arabica origin (Pinto-Maglio and Cruz, 1987), the establishment of the first karyogram and ideogram for C. arabica based on pachytene chromosomes (Pinto-Maglio and Cruz, 1998), following studies in several diploid species to determine the nuclear content (Cros et al, 1998), the heterochromatin localization and quantification in mitotic chromosomes (Pierozzi et al, 1999) and subsequently the heterochromatin molecular composition, as reviewed by Pinto-Maglio (2006) and Hamon et al (2009). The first approaches in coffee chromosome studies however concerned the establishment of chromosome number which led to the finding that wild species are diploid (2n=22) while the Arabica varieties and cultivars are predominantly tetraploid (2n=44) with several hexaploid (2n=66) and octoploid (2n=88) exceptions (Krug, 1934(Krug, , 1945.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using the sensitive fluorescence in situ hybridization (FISH) technique, especially with nuclear ribosomal RNA (rRNA) genes as probes, has been proven to be efficient for the investigation of species with small or similarly sized chromosomes (Leitch and Heslop-Harison, 1992;Garcia et al 2012). Thus, this enables the identification and discrimination of different chromosomes within and between chromosome complements (Hamon et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Bouharmont (1959Bouharmont ( , 1963, Pinto-Maglio and Cruz (1998), Campa et al (2003), Lombello and Pinto-Maglio (2004a, 2004b, 2004c, Hamon et al (2009) and Razafinarivo et al (2012). The studies regarding the total amount of DNA showed similarities between C. congensis and C. liberica (1.53 pg/1.54 pg and 1.59 pg, respectively) and also between C. eugenioides and C. stenophylla (1.36 pg/1.45 pg and 1.28 pg, respectively), despite the differences between these two pairs of species (Cros et al 1994;Noirot et al 2003;Razafinarivo et al 2012).…”
Section: Discussionmentioning
confidence: 99%